PHYTOCHEMICAL SCREENING OF ETHANOLIC EXTRACT: a Preliminary Test on Five Medicinal Plants on Bangkalan - Laila Khamsatul Muharrami; Fatimatul Munawaroh; Taslim Ersam; Mardi Santoso (JURNAL PENA SAINS, 2020)
This study is preliminary research of secondary metabolite potential from medicinal Herb Madura. This study aims to know the medicinal plants used in the medicinal herb Madura and the phytochemical content contained in these medicinal plants.  The method used in this study is a survey to know the kinds of medicinal plants used in Madura Herb. Then a phytochemical screening test for the medicinal plant was performed. The phytochemical screening test used are alkaloids, steroids, saponins, and flavonoids.  Based on the research, it is found that 66 medicinal plants are widely used for "Ramuan Madura” in  Bangkalan. Of the 66 plants selected, Madura five medicinal plants widely used by the Madurense; Parameria laevigata, Kaempferia galanga L., Curcuma domestica, Curcuma xanthorrhiza, dan Punica granatum. Then the preliminary phytochemical test to determine the secondary metabolite compounds. Secondary metabolite content obtained include alkaloids, saponins, steroids, and flavonoids.